Paclobutrazol and water restriction on the growth and development of coffee plants - Ribeiro, André Felipe Fialho; Matsumoto, Sylvana Naomi; Ramos, Paula Acácia Silva; Santos, Jefferson Luan Dias dos; Teixeira, Ednilson Carvalho; d’Arêde, Lucialdo Oliveira; Viana, Anselmo Eloy Silveira (Coffee Science - ISSN 1984-3909, 2017)
Paclobutrazol can mitigate the negative effects of water stress in many plant species, however, for coffee plants is necessary to expand the knowledge base on the subject. In this research it was aimed to evaluate the morphophysiology of young plants of Coffea Arabica cv. ‘Catuaí Vermelho IAC 144’ in response to different water regimes and paclobutrazol concentrations applied in the soil. The trial was carried out in a greenhouse at Vitória da Conquista, BA. The experimental design was a randomized block with factorial arrangement represented by five concentrations of paclobutrazol (0, 50, 100, 150 and 200 mg L-1) applied in the soil and two water regimes (with and without water restriction) in five replicates.At 120 days after the application of plant growth regulator was evaluated the water status, the SPAD index and the morphological characteristics of plants. The application of paclobutrazol reduced the SPAD index and individual leaf area, and favored the water status of coffee plants under water restriction. The young coffee plants without water restriction and treated with the plant growth regulator, had higher leaf retention and SPAD index, and lowest individual leaf area. Paclobutrazol at high concentrations resulted in plants more compact. The water restriction provided less total leaf area, number of branches and dry weight of the coffee.